The Effect of Gibberellin on Somatic Embryo Growth and Maturation and Plantlet Regeneration of Tangerine (Citrus reticulata Blanco.) var. Batu 55 - Firdiana, Elok Rifqi; Indriyani, Serafinah; Widoretno, Wahyu (Graduate School, Universitas Brawijaya, 2015)
The effect of gibberellin at multiplication stage on somatic embryo growth and maturation and plantlet regeneration of tangerine (Citrus reticulata Blanco.) var. Batu 55 was assessed. Somatic embryo at globular phase was cultured on MT media + 30 gL-1 sucrose and various concentrations of gibberellin (0, 2, 4, 6, and 8 ppm). The somatic embryo was maturated on MT media + 500 ppm malt extract + 73 mM sorbitol + 73 mM galactose. Cotyledonary somatic embryo was regenerated into plantlet on MT media + 500 ppm malt extract + 30 gL-1 sucrose + 2 ppm GA3. The results showed that the addition of gibberellin in somatic embryo multiplication stage increased somatic embryo growth and maturation and plantlet regeneration of tangerine. Optimum concentration of gibberellin needed for somatic embryo growth was 4 ppm which yielded two-fold fresh weight compared to control. The percentage of maturation was very low below 5%. The addition of gibberellin in media at embryo multiplication stage slightly increased the percentage of maturation about 1-2%. Thirty percent of cotyledonary embryo was able to regenerate into plantlet. The addition of gibberellin in media at embryo multiplication stage increased the regeneration percentage, even the addition of 8 ppm gibberelline yielded regeneration percentage up to 70%.Keywords: gibberellin, growth, maturation, plantlet regeneration, somatic embryo